Treatment with combined dabrafenib and trametinib in BRAFV600E-mutated metastatic malignant melanoma: a case of long-term complete response after treatment cessation - Sonia Brugnara; Mariacristina Sicher; Elena Maria Bonandini; Davide Donner; Franca Chierichetti; Mattia Barbareschi; Carlo Renè Girardelli; Orazio Caffo (Drugs in Context, 2018)
Here, we report the case of a patient, diagnosed with BRAFV600E-mutated metastatic malignant melanoma M1a, who achieved a complete metabolic response after 7 months of treatment with the combination of dabrafenib and trametinib. After 31 months, the treatment was interrupted for patient’s decision. To date October 2017, 18 months after the interruption of the treatment with the combination of dabrafenib and trametinib, follow-up Positron Emission Tomography (PET) scans are still documenting complete metabolic response.